Understanding neurocognitive recovery in older adults after total hip arthroplasty—neurocognitive assessment, blood biomarkers and patient experiences: a mixed-methods study - Ulrica Nilsson; Karin Liander; Lina Bergman; Anahita Amirpour; Jeanette Eckerblad; Gabriela Markovic (BMJ Open)
Objective Delayed neurocognitive recovery, previously known as postoperative cognitive dysfunction, is a common complication affecting older adults after surgery. This study aims to address the knowledge gap in postoperative neurocognitive recovery by exploring the relationship between subjective experiences, performance-based measurements, and blood biomarkers.Design Mixed-methods study with a convergent parallel (QUAL+quan) design.Setting and participants The study reports results from 40 older adult patients (52.5% women; mean age 73, SD 6.7) scheduled for total hip arthroplasty at a hospital in Sweden.Outcome measures Neurocognitive performance was assessed using a standardised test battery, neuroinflammation through blood biomarker analysis and postoperative neurocognitive recovery via semistructured interviews and the Swedish Quality of Recovery questionnaire.Results Five patients were classified as having delayed neurocognitive recovery based on performance tests. Qualitative data revealed that most patients reported cognitive symptoms, particularly related to executive functions and fatigue. Psychological factors, including a sense of agency and low mood, significantly influenced cognitive recovery and daily functioning. Elevated inflammatory blood biomarkers were not detected pre- or postoperatively in patients with delayed neurocognitive recovery. The global postoperative recovery score was 40.9, indicating a low quality of recovery.Conclusion Many patients reported subjective cognitive decline that was not corroborated by delayed neurocognitive recovery in the performance-based tests. Psychological factors were influential for neurocognitive recovery and should be routinely assessed. Future research should incorporate longitudinal follow-ups with performance-based measurements, fatigue assessment, evaluations of instrumental activities of daily living and subjective reporting, supported by a multidisciplinary team approach.Trial registration number NCT05361460.